Exploratory spatial transcriptomic profiling of peritumoral Th2 immune polarization in HPV-positive oropharyngeal cancer - Wakisaka, Naohiro; Moriyama-Kita, Makiko; Kondo, Satoru; Kobayashi, Eiji; Ueno, Takayoshi; Nakanishi, Yosuke; Endo, Kazuhira; Sugimoto, Hisashi; Yoshizaki, Tomokazu (Frontiers in Oncology, 2025)
IntroductionOropharyngeal squamous cell carcinoma (OPC) associated with high-risk human papillomavirus (HPV), particularly HPV-16, generally shows favorable outcomes yet paradoxically exhibits a high incidence of early lymphatic metastasis. The immune mechanisms underlying this phenomenon remain unclear.MethodsWe conducted an exploratory spatial transcriptomic analysis using the GeoMx Digital Spatial Profiler on formalin-fixed, paraffin-embedded samples from six patients with palatine tonsil-derived OPC. Tumor tissue regions (TTRs) and lymphoid follicular regions (LFRs) were compared according to HPV status and nodal involvement.ResultsIn HPV-positive LFRs, pathways related to B-cell apoptosis appeared downregulated, suggesting prolonged B-cell survival and antigen presentation. Metastasis-negative HPV-positive cases displayed a Th2-skewed immune profile in LFRs, with increased naïve B cells, plasma cells, eosinophils, M2 macrophages, and activated mast cells. In contrast, metastasis-positive cases showed increased T cell activation in LFRs and reduced proliferation-related signaling in TTRs. Pathways involving estrogen signaling and bile acid metabolism were also associated with metastatic behavior.ConclusionThese exploratory findings suggest that peritumoral Th2-biased immunity within lymphoid structures may contribute to restraining lymphatic metastasis in HPV-positive OPC. Spatial transcriptomics may provide a high-resolution framework for investigating tumor–immune interactions and generating hypotheses for future mechanistic and clinical studies.